Church Forests Diversity and Biomass Carbon Stock along Urbanization Continuum in Dangila District, Awi-Zone, Ethiopia - Geremew Bitew Sewagegn; Dagm Fikir Abate (International Journal of Forestry Research)
Ethiopian Orthodox Tewahido Church forest plays a significant role in native species conservation, carbon sequestration, and climate change mitigation. The study was carried out to determine woody species diversity and biomass carbon stock of Church forests along the urbanization continuum in Dangila Woreda, Awi-Zone, Ethiopia. After a preliminary survey, the churches were grouped into urban, peri-urban, and rural continuums. From each group, one Church was purposively selected for each urbanization continuum based on accessibility for making a total of nine sample churches. Tree height and diameter data were recorded from a 2 m width of systematically laid down Gentry transect lines; seedlings were counted from three plots of 2 m × 2 m size at each transect line. The similarities along urbanization were calculated using Sorenson’s similarity index. ANOVA was then used to test for differences across the continuum. Finally, a total of 62, 57, and 73 woody species were identified in urban, per-urban, and rural Church forest. The mean Shannon diversity for each urban, peri-urban, and rural Church forest was 2.38, 2.67, and 2.90, respectively. The general pattern of woody species community structure for each urbanization continuum shows an inverted J-shape. The biomass carbon stock along the urban, peri-urban, and rural continuum was 24.96, 77.38, and 46.13 tons/ha, respectively. Therefore, Church forests play an indispensable role in woody species conservation, carbon sequestration, and climate change mitigation at each urbanization continuum.